Análise de uma biblioteca de mutantes de Xanthomonas citri subsp. citri quanto à patogenicidade - Silva, Ana Carolina Buzinari da [UNESP] (2014)
The study of plant-pathogen interaction is very important to citrus canker understanding, justifying the search for virulence and pathogenicity related genes in Xanthomonas citri subsp. citri (Xac), causal agent of this disease. In this study, a random mutagenesis by Tn5 transposon insertion into Xac’s genome was performed. Eight thousand mutants were produced and 292 mutants were tested in planta. From those, five mutants expressed altered symptomatology, two showed complete absence of symptoms and three reduced hyperplasia. Gene sequences analysis where transposon was inserted, indicated mutations in purF, yapH and oar genes, in a region that codes for a hypothetical protein (XAC0196), and in a region between pobB (XAC0362) and glpR (XAC0361) genes. Analysis of bacteria growth curve in planta showed that, except for purF gene, all the others genes may be involved in Xac pathogenicity. Two of these genes, yapH and oar, are described as bacterial adhesion related genes, highlighting that interference in this process has direct influence in the Xac infection success. The importance of hypothetical protein identification is emphasized, since it presented attenuated symptomatology when mutated